Suppression of transforming growth factor-β by mesenchymal stem-cells accelerates liver regeneration in liver fibrosis animal model - Sa’dyah, Nur Anna C; Putra, Agung; Dirja, Bayu Tirta; Hidayah, Nurul; Yasmine Azzahara, Salma; Candra Satria Irawan, Risky (Universa Medicina, 2021)
IntroductionLiver fibrosis (LF) results from the unregulated chronic wound healing process in liver tissue. Transforming growth factor-beta (TGF-β) is the major contributing cytokine of LF promotion through activation of quiescent hepatic stellate cells (HSCs) into myofibroblasts (MFs) and increased extracellular matrix (ECM) deposition such as collagen leading to scar tissue development. Mesenchymal stem cells (MSCs) have an immunomodulatory capability that could be used as a new treatment for repairing and regenerating LF through suppression of TGF-β. This study aimed to examine the role of MSCs in liver fibrosis animal models through suppression of TGF-β levels without scar formation particularly in the proliferation phase.MethodsIn this study, a completely randomized design was used with sample size of 24. Male Sprague Dawley rats were injected intraperitoneally (IP) with carbon tetrachloride (CCl4), twice weekly, for eight weeks to induce LF. Rats were randomly assigned to four groups: negative control, CCl4 group, and CCL4 + MSC-treated groups T1 and T2, at doses of 1 x 106 and 2x106 cells, respectively. TGF-β levels were analyzed by enzyme-linked immunosorbent assay (ELISA). One-way ANOVA and a least significant difference (LSD) was used to analyse the data. ResultsThe TGF levels of LF rat models decreased on day 7 after MSC administration. The levels of TGF-β in both MSC groups T1 and T2 decreased significantly compared with the control group (p<0.05). The TGF-β suppression capability of T2 was optimal and more significant than that of T1.ConclusionMSCs can suppress TGF levels in liver fibrosis induced rats.